PEMBELAJARAN FISIKA DI SMA DENGAN MENGGUNAKAN MODEL KOOPERATIF TIPE STAD (KAJIAN: DI SMAN 1 TAPEN BONDOWOSO) - Puri Nur’aini Agustin; Albertus Djoko Lesmono; Rayendra Wahyu Bachtiar (JURNAL PEMBELAJARAN FISIKA, 2017)
This research was the result of research entitled "Learning Physics in senior high school by Using the Cooperative Model Type STAD (Study: at SMAN 1 Tapen Bondowoso)". The purpose of this research was to know the effect of using STAD on students’ motivation in learning physic and to know wheter or not there was an effect of using STAD on the result of students’ learning outcome in learning physic at senior high school. The population of this research was the tenth grade students of SMAN 1 Tapen Bondowoso. The design of this research was quasi experimental research post test only control design. The data was collected through students’ motivation and students’ learning outcomes by using questionnaire, observation, interviews and documentation. Based on the statistical results, it was known that the mean score of students’ motivation and learning outcome in experimental class was better than the students’ in the control class. It can be concluded that there was an effect of using cooperative learning model STAD on the students’ motivation and learning outcome in learning physics at SMAN 1 Tapen Bondowoso. Keywords : cooperatif type STAD model, students’ motivation, student’s learning outcome